Diazirine-functionalized mannosides for photoaffinity labeling: trouble with FimH - Beiroth, Femke; Koudelka, Tomas; Overath, Thorsten; Knight, Stefan D.; Tholey, Andreas; Lindhorst, Thisbe K. (Beilstein Journal of Organic Chemistry, 2018)
Photoaffinity labeling is frequently employed for the investigation of ligand–receptor interactions in solution. We have employed an interdisciplinary methodology to achieve facile photolabeling of the lectin FimH, which is a bacterial protein, crucial for adhesion, colonization and infection. Following our earlier work, we have here designed and synthesized diazirine-functionalized mannosides as high-affinity FimH ligands and performed an extensive study on photo-crosslinking of the best ligand (mannoside 3) with a series of model peptides and FimH. Notably, we have employed high-performance mass spectrometry to be able to detect radiation results with the highest possible accuracy. We are concluding from this study that photolabeling of FimH with sugar diazirines has only very limited success and cannot be regarded a facile approach for covalent modification of FimH.
Keywords: diazirines; docking; FimH; lectin ligands; mannosides; mass spectrometry; photoaffinity labelling

(untitled) - Robinette, D.; Neamati, N.; Tomer, K. B.; Borchers, C. H. (Expert Rev. Proteomics, 2006)

(untitled) - Sumranjit, J.; Chung, S. J. (Molecules, 2013)

(untitled) - Smith, E.; Collins, I. (Future Med. Chem., 2015)

(untitled) - Murale, D. P.; Hong, S. C.; Haque, M. M.; Lee, J.-S. (Proteome Sci., 2017)

(untitled) - Dubinsky, L.; Krom, B. P.; Meijler, M. M. (Bioorg. Med. Chem., 2012)

(untitled) - Hashimoto, M.; Hatanaka, Y. (Eur. J. Org. Chem., 2008)

(untitled) - Brunner, J.; Senn, H.; Richards, F. M. (J. Biol. Chem., 1980)

(untitled) - Hatanaka, Y.; Hashimoto, M.; Kurihara, H.; Nakayama, H.; Kanaoka, Y. (J. Org. Chem., 1994)

(untitled) - Walter, M.; Lindhorst, T. K. (Synthesis, 2006)

(untitled) - Walter, M.; Wiegand, M.; Lindhorst, T. K. (Eur. J. Org. Chem., 2006)

(untitled) - Wiegand, M.; Lindhorst, T. K. (Eur. J. Org. Chem., 2006)

(untitled) - Sakurai, K.; Yasui, T.; Mizuno, S. (Asian J. Org. Chem., 2015)

(untitled) - Knight, S. D.; Bouckaert, J. (Top. Curr. Chem., 2009)

(untitled) - Hartmann, M.; Lindhorst, T. K. (Eur. J. Org. Chem., 2011)

Synthesis and Biological Applications of Glycoconjugates - Lindhorst, T. K. (Bentham Science e-Books, 2011)

(untitled) - Flores-Mireles, A. L.; Walker, J. N.; Caparon, M.; Hultgren, S. J. (Nat. Rev. Microbiol., 2015)

(untitled) - Kleeb, S.; Pang, L.; Mayer, K.; Eris, D.; Sigl, A.; Preston, R. C.; Zihlmann, P.; Sharpe, T.; Jakob, R. P.; Abgottspon, D.; Hutter, A. S.; Scharenberg, M.; et al. (J. Med. Chem., 2015)

(untitled) - Wurpel, D. J.; Totsika, M.; Allsopp, L. P.; Webb, R. I.; Moriel, D. G.; Schembri, M. A. (Proteomics, 2016)

(untitled) - Sperling, O.; Fuchs, A.; Lindhorst, T. K. (Org. Biomol. Chem., 2006)

(untitled) - Fiege, B.; Rabbani, S.; Preston, R. C.; Jakob, R. P.; Zihlmann, P.; Schwardt, O.; Jiang, X.; Maier, T.; Ernst, B. (ChemBioChem, 2015)

(untitled) - Kramer, B.; Metz, G.; Rarey, M.; Lengauer, T. (Med. Chem. Res., 1999)

(untitled) - Rarey, M.; Kramer, B.; Lengauer, T.; Klebe, G. (J. Mol. Biol., 1996)

(untitled) - Rarey, M.; Kramer, B.; Lengauer, T. (J. Comput.-Aided Mol. Des., 1997)

Tripos Inc. SYBYL, 6.9 (Tripos Inc., 2002)

(untitled) - Connolly, M. L. (Science, 1983)

(untitled) - Chernyak, A. Y.; Sharma, G. V. M.; Kononov, L. O.; Krishna, P. R.; Levinsky, A. B.; Kochetkov, N. K.; Rao, A. V. R. (Carbohydr. Res., 1992)

(untitled) - Šardzík, R.; Noble, G. T.; Weissenborn, M. J.; Martin, A.; Webb, S. J.; Flitsch, S. L. (Beilstein J. Org. Chem., 2010)

(untitled) - Nassal, M. (Liebigs Ann. Chem., 1983)

(untitled) - Kumar, A. B.; Tipton, J. D.; Manetsch, R. (Chem. Commun., 2016)

(untitled) - Gee, C. T.; Arntson, K. E.; Urick, A. K.; Mishra, N. K.; Hawk, L. M. L.; Wisniewski, A. J.; Pomerantz, W. C. K. (Nat. Protoc., 2016)

(untitled) - Bouckaert, J.; Berglund, J.; Schembri, M.; De Genst, E.; Cools, L.; Wuhrer, M.; Hung, C.-S.; Pinkner, J.; Slättegård, R.; Zavialov, A.; Choudhury, D.; Langermann, S.; et al. (Mol. Microbiol., 2005)